Aboriginal perceptions of social and emotional wellbeing programs: A systematic review of literature assessing social and emotional wellbeing programs for Aboriginal and Torres Strait Islander Australians perspectives. (16th November 2018) - Murrup‐Stewart, Cammi; Searle, Amy K.; Jobson, Laura; Adams, Karen
Abstract : Australian Aboriginal and Torres Strait Islander communities have been targets of social and emotional wellbeing programs for many years. However, the few health‐care programs and services that are evaluated rarely provide insight into the participants' perspectives of program success or failure. This systematic review assessed 33 social and emotional wellbeing programs across Australia to better understand what Aboriginal community members think about the programs and how they could be improved. Results highlighted the interesting and valuable insights provided by Aboriginal participants, including what kinds of program activities and approaches are most suitable, what program characteristics are successful or desired, and their experiences of wellbeing change before and after program participation. They likewise voiced opinions about poorly received programs, culturally inappropriate services and negative experiences. This review highlighted how health and wellbeing programs must better engage Aboriginal and Torres Strait Islander clients to ensure that services are culturally safe, holistic, integrate appropriate staffing, include culturally relevant activities and value patient/participant experiences. These findings have significant implications for the health and wellbeing sector; specifically, research, policy, program design and implementation, evaluation methods, and self‐determination.